Antioxidant, phytochemical, and therapeutic properties of medicinal plants: a review - Onyenibe Sarah Nwozo; Enor Magdalene Effiong; Patrick Maduabuchi Aja; Chinaza Godswill Awuchi (International Journal of Food Properties)
Oxidation is an integral part of aerobic processes of life. It involves the transfer of electrons or hydrogen via a chemical reaction from a substance to an oxidizing agent leading to the production of free radicals. These free radicals which are highly reactive in turn initiate a chain of reactions that lead to cellular damage. The etiology of plethora diseases has been linked to the generation of free radicals beyond the body’s antioxidant capacity, leading to oxidative stress. Consequently, the focus of research has tilted toward plants which provide natural products rich in antioxidants capable of scavenging and distrupting the harmful effects of these free radicals. A large group of compounds produced by plants referred to as phytochemicals possessing high antioxidant properties have been seen to be helpful in tackling numerous diseases. This review covered the antioxidant potential of some plants with medicinal properties beneficial to people, industries, and health institutions who desire their potential benefits. A total of two hundred and fifty plants from the following families; Asteraceae, Combretaceae, Euphorbiaceae, Fabaceae, Lamiaceae, Moraceae and Malvaceae were reviewed. These plants exert important biological properties, such as anti-inflammatory, antioxidant, immunomodulatory, anticancer, and antimicrobial properties, among others.